Thirteen new species of the spider genus Karaops (Araneae: Selenopidae) from Western Australia - Crews, Sarah C. (Zootaxa, 2013)
Thirteen new species of the recently-described genus Karaops Crews and Harvey, 2011 are described from Western Aus-tralia, bringing the total number of species of this genus to 37. The new species are K. umiida sp. nov. (♀,♂), K. nyiyaparli sp. nov. (♀), K. kariyarra sp. nov. (♀), K. yurlburr sp. nov. (♀,♂), K. feedtime sp. nov. (♀), K. forteyi sp. nov. (♀,♂), K. yindjibarndi sp. nov. (♂), K. jaburrara sp. nov. (♂), K. ngarluma sp. nov. (♂), K. nyangumarta sp. nov. (♀,♂), K. nyamal sp. nov. (♀), K. banyjima sp. nov. (♀) and K. yumbu sp. nov. (♂). The male of K. martamarta Crews and Harvey, 2011 is described for the first time, and new distribution records are given for this species and for K. burbidgei Crews and Har-vey, 2011. Finally, a new key to all of the described species of Karaops is provided.